2023
DOI: 10.5005/jp-journals-10071-24419
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neutrophil Gelatinase-associated Lipocalin (NGAL) and Other Clinical Parameters as Predictors of Bacterial Sepsis in Patients Presenting to the Emergency Department with Fever

Abstract: A bstract Background Bacterial sepsis is associated with significant morbidity and mortality. However, to date, there is no single test that predicts sepsis with reproducible results. We proposed that using a combination of clinical and laboratory parameters and a novel biomarker, plasma neutrophil gelatinase-associated lipocalin (NGAL) may aid in early diagnosis. Method A prospective cohort study was conducted at a tertiary care center in Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Another study of 100 septic patients, 37 of whom had bacterialtype sepsis, found the standard plasma NGAL cut-off value for predicting sepsis to be 570 ng/mL, AUC 0.69. The use of NGAL > 570 ng/mL with scores (diabetes mellitus, presence of chills, rapid sequential organ failure assessment (qSOFA) score > 2 and clear focus of infection) > 7 was predominantly suggestive of bacterial infection with the interval likelihood ratio (LR) of 7.77 [53]. In a neonatal population, a similar cut-off value of 455 µg/L (sensitivity 71.4%, specificity 100%) and 1104 µg/L (sensitivity 39.3%, specificity 95.2%) was found to anticipate sepsis and non-survival, respectively [54].…”
Section: Neutrophil Gelatinase-associated Lipocalin-ngalmentioning
confidence: 99%
“…Another study of 100 septic patients, 37 of whom had bacterialtype sepsis, found the standard plasma NGAL cut-off value for predicting sepsis to be 570 ng/mL, AUC 0.69. The use of NGAL > 570 ng/mL with scores (diabetes mellitus, presence of chills, rapid sequential organ failure assessment (qSOFA) score > 2 and clear focus of infection) > 7 was predominantly suggestive of bacterial infection with the interval likelihood ratio (LR) of 7.77 [53]. In a neonatal population, a similar cut-off value of 455 µg/L (sensitivity 71.4%, specificity 100%) and 1104 µg/L (sensitivity 39.3%, specificity 95.2%) was found to anticipate sepsis and non-survival, respectively [54].…”
Section: Neutrophil Gelatinase-associated Lipocalin-ngalmentioning
confidence: 99%